Fire Safety in Industrial Facilities: Features and Requirements of Safety Systems (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article discusses the fire safety threats in industrial facilities and the measures to mitigate them. The main fire safety threats identified in the article include electrical systems, technological processes, heat sources, combustible and explosive materials, non-compliance with fire safety regulations, mechanical damage, and natural disasters. The article also emphasizes the requirements for fire extinguishing systems in industrial facilities, the importance of using modern technologies, and the necessity of training employees. It highlights the advantages and necessity of using fire extinguishing systems with automation. As a result, the article emphasizes the importance of properly selected, installed, and regularly maintained fire extinguishing systems to minimize fire risks and ensure safety in industrial facilities.